The effects of stimulant medications on children’s growth velocity - Siddiqi, Siraj; Dedlow, E Rosellen; Saliba, Heidi; Black, Erik W; Giordano, Beverly P (Indian Journal of Child Health, 2014)
Objective: This study sought to determine whether relationships exist between stimulant medications and children’s growth velocity. Methods: The investigators conducted a retrospective review of 280 charts of pre-pubertal children with attention-deficit hyperactivity disorder (ADHD) who were prescribed stimulant medications for a minimum of 1 year. The children were patients in a university child development/ADHD clinic. Results: The average growth velocity across all genders and ages was 5.72 cm/year (females 5.53 cm/year, males 5.28 cm/year). The majority of the children had growth velocities in the 25-50th percentiles for age. Conclusion: This study did not find evidence of significant effect on growth velocity in children with ADHD treated with stimulant medications. Our results concur with the majority of other studies of growth in children taking stimulant medications for ADHD management. It supports our continued prescription of stimulant medications without concern for slowed or stunted growth in our patients with ADHD.